2003
DOI: 10.1002/app.12446
|View full text |Cite
|
Sign up to set email alerts
|

Rubber seed oil modified with maleic anhydride and fumaric acid and their alkyd resins as binders in water‐reducible coatings

Abstract: Rubber seed oil (RSO) was modified with different amounts of maleic anhydride, and RSO alkyds (50% oil length) were modified to various extents by the incorporation of different amounts of maleic anhydride and fumaric acid. All the resins were evaluated as water-reducible binders. Modification with maleic anhydride increased the acid and saponification values of RSO but reduced the iodine value. RSO modified with maleic anhydride exhibited lower amounts of volatile organic compounds (Ͻ20 g/L) than the correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 12 publications
(17 reference statements)
0
19
0
1
Order By: Relevance
“…All these characteristic quality features of RSO are exploited in the production of environmentally friendly solventborne and water-reducible coatings (15)(16)(17) and in other industrial uses (18,19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these characteristic quality features of RSO are exploited in the production of environmentally friendly solventborne and water-reducible coatings (15)(16)(17) and in other industrial uses (18,19).…”
Section: Resultsmentioning
confidence: 99%
“…This study concerns the characterization of rubber seed oil (RSO), which is assuming prominence as a binder in surface coatings and as a plasticizer/stabilizer for PVC and natural rubber (15)(16)(17)(18)(19). Characterization and determination of the quality features that would distinguish RSO from other vegetable oils were carried out using GPC, GLC, and FTIR and NMR spectroscopy as well as chemical analyses.…”
mentioning
confidence: 99%
“…Aigbodion et al [17,18] reported the preparation of WB coating from maleinated and fumarised rubberseed oil. Fish oil and linseed oil modified polyurethane dispersion (PUD) have shown good coating properties as reported by Nimbalker and Athawale [19].…”
Section: Introductionmentioning
confidence: 99%
“…Then, maleinized rubber seed oils were used to prepare watersoluble alkyd samples. In another set of experiments, rubber seed oil (RSO) was also modified with different amounts of maleic anhydride, and RSO alkyds (50% oil length) were modified to various extents by the incorporation of different amounts of maleic anhydride and fumaric acid [18]. All the resins were evaluated as water-reducible binders.…”
Section: Synthesis Of Water Soluble Maleinized Oilsmentioning
confidence: 99%